Tepung Tempe Kaya Isoflavon Meningkatkan Kadar Kalsium, Posfor dan Estrogen Plasma Tikus Betina Normal - Suarsana, I Nyoman; Sadra Dharmawan, I Nyoman; Gorda, I Wayan; Pontjo Priosoeryanto4, Bambang (Jurnal Veteriner, 2012)
This research aimed to study the effect of isoflavon-riched tempe flour on calcium (Ca, phosphate(P), and estrogen levels in plasma et normal female rats during their growth period. A level oftwenty-five 2 months old female Sprague Dawley rats with an avarage body weight of 200 g wasrandomly divided into into 5 groups: one with control group (KO: without treatment) and fourtreatment groups (K1, K2, K3, K4 : animals were given tempe flour with isoflavon at 1; 2; 4; and 6 mg/200 g/bw, respectively). The treatment was conducted for two months, following this blood plasmawas collected to analyse the level of calcium, phosphor, and estrogen, respectively. The resultshowed that although the plasma level of Ca, P, and estrogen was higher in the treatment groupcompare to the control group, this was not significantly different (P>0,05). The highest plasmalevel of Ca, P, and estrogen was seen in anmal receiving tempe flour with 4 mg/ 200 g bw/dayisoflavon.
Keywords: Tempe flour, isoflavon, calcium, phosphor, estrogen.